MENINGKATKAN DISIPLIN PENDIDIK DAN TENAGA KEPENDIDIKAN MELALUI STRATEGI COUCHING DI SDN GIRIWINAYA - Nuraini, Ani; Mulyadi, Budi; Taryana, Iwan; Itang, Itang; Yoseptry, Ricky (PENDIDIKAN SAINS DAN TEKNOLOGI, 2025)
The purpose of writing this paper is to address the stagnation of discipline among teachers and educational staff (GTK) at SDN Giriwinaya, Warungkondang District, Cianjur Regency, in carrying out their daily tasks as professional GTKs. The efforts made by the school principal aim to realize their roles and functions in accordance with the mandate of the Minister of Education and Culture Regulation No. 13 of 2007 on the Competencies of School/Madrasah Heads, which states that every school/madrasah head must meet five competency aspects: personality, managerial, supervisory, entrepreneurship, and social. The writing method of this paper is based on empirical experiences while serving as a school principal, supplemented by the author's experience during the Teacher Empowerment Program organized by the Ministry of Education and Culture for the 8th batch in 2023. The discipline of GTK, which has been perceived as lacking in accompanying students in the teaching and learning process, has resulted in a decline in the community's trust in sending their children to SDN Giriwinaya. This has also impacted the quality of graduates, which has yet to show satisfactory results. By analyzing the events experienced during the leadership in the school, the author applies a strategy to discipline GTK through coaching with a humanistic approach, which was carried out throughout the leadership process.